Website for the treatment of the sociocultural component of the English language - Alonso Águila, Guillermo; Artiles Díaz, Wilfredo; de la Paz Gálvez, Eida (Varela Journal, 2021)
The globalization of communication together with the development of technologies have virtually shortened distances, bringing people of different languages and cultures closer together than ever before in history. The teaching of foreign languages in Cuba has ignored the treatment of the sociocultural component of the language for years, although this has been defined in theory as an essential component of communicative competence, a central objective of language teaching, which recently, the adjective intercultural has been added. Currently the means available to students are not effective for the development of this competence and respond ineffectively to the interests of the present generation. Consequently, a website was developed to improve the treatment of the sociocultural component related to English-speaking peoples in the career of the Bachelor of Education in Foreign Languages with which a greater motivation was achieved towards learning the culture and a level incipient development of students’ intercultural communicative competence.